Mouvement vers le bas: (se) baisser - Cholewa, Joanna (Kalbotyra, 2021)
This article aims to disambiguate the French verb baisser, which describes the downward movement of an entity, and to present its conceptual structure. Our approach is strongly based on the belief that the meaning of the word is conceptual, and that it reflects the world being looked at, not the real world (Honeste 1999, 2005). Our interest will focus on the locative and abstract meanings of the chosen verb, the uses of which we will study. Each use is a set formed by a predicate, defined by its arguments whose field is delimited by the predicate itself (Gross 2015). Arguments are defined using object classes. Each use is illustrated by a single sentence and a translation into Polish, the translation being a synonym of a word in another language. The type of event described by the verb will be studied, taking into account: the situation described by the verb (kinematic, dynamic, according to Desclés 2003, 2005); belonging to one of the four groups of verbs of movement, distinguished by Aurnague (2012) according to two parameters: change of location and change of elementary locative relwation; polarity (initial, median and final, according to Borillo 1998). Baisser has twelve uses (locative and abstract). Their invariant meaning is downwards movement, which is conceptualized in different ways: displacement of an entity downwards in physical space, but also as a decrease along a scale: of quantifiable value, of sound, of luminosity, intensity or quality, and finally of physical strength and of quality.